2008
DOI: 10.1002/mds.22057
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rest‐activity rhythm is altered in Parkinson's disease patients with hallucinations

Abstract: The sleep-wake cycle in Parkinson's Disease (PD) is profoundly disrupted, but less is known about circadian rhythm in PD and its relationship to other important clinical features. This study compared rest-activity rhythms in healthy older adults and PD patients with and without hallucinations. Twenty-nine older adults and 50 PD patients (27 with hallucinations, 23 without) were assessed using wrist-worn actigraphy for 5 days. Disease-related and cognitive data were also collected. PD patients demonstrated redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 35 publications
2
78
1
1
Order By: Relevance
“…In order to investigate differences in physical activity between these two subgroups, we measured physical activity using actigraphy. Previous studies have reported the usefulness of standard actigraphy to assess fluctuation of akinesia [23], tremor, motor fluctuation [24], and sleep in PD patients [25,26]. In the present study, measured activity counts in the PD group were higher compared to the MPS-severe group.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In order to investigate differences in physical activity between these two subgroups, we measured physical activity using actigraphy. Previous studies have reported the usefulness of standard actigraphy to assess fluctuation of akinesia [23], tremor, motor fluctuation [24], and sleep in PD patients [25,26]. In the present study, measured activity counts in the PD group were higher compared to the MPS-severe group.…”
Section: Discussioncontrasting
confidence: 45%
“…Those subjects with unilateral PD wore monitors on their least affected side. This placement has been shown to better represent whole-body movement [25] and was intended to reduce artifacts such as low level constant activity when writing with the dominant hand or dyskinesias in the most affected arm. At the same time, all participants completed a sleep log for 7 days.…”
Section: Measurement Of Physical Activity Using Actigraphymentioning
confidence: 99%
“…Previous studies have evidenced a number of circadian rhythm alterations in PD patients (Ferreira et al, 2006;Garcia-Borreguero et al, 2003;Lees et al, 1988;van Hilten et al, 1993;Whitehead et al, 2008;Willis, 2008b), in line with the changes observed in a number of circadian rhythm parameters in different experimental PD models, including the 6-OHDA and the MPTP animal models (Almirall et al, 2001;Ben et al, 1999;Ben & Bruguerolle, 2000). In this study, we assessed whether rotenone-induced parkinsonism is associated with alterations of circadian rhythms.…”
Section: Discussionmentioning
confidence: 63%
“…PD patients often exhibit sleep disorders, such as excessive daytime somnolence and nighttime sleep fragmentation (Ferreira et al, 2006;Garcia-Borreguero et al, 2003;Lees et al, 1988;van Hilten et al, 1993). Actigraphy studies show increased levels of nocturnal motor activity and an increased proportion of time with movement in PD patients (van Hilten et al, 1994), which suggests a more disturbed sleep as well as a lower amplitude rest-activity rhythm with increased intradaily variability as compared to healthy adults (Whitehead et al, 2008). Moreover, PD patients exhibit alterations in various circadian patterns, such as in melatonin (Bordet et al, 2003) and cortisol (Hartmann et al, 1997) secretion, core body temperature (Bordet et al, 2003;Pierangeli et al, 2001), and heart rate variability (Pursiainen et al, 2002), among others.…”
Section: Introductionmentioning
confidence: 96%
“…A number of studies found an association between visual hallucinations and RBD, 16,21,36,37 and in one study RBD was a predictor of future psychosis. 13 Additionally, compared to those without hallucinations, PD subjects with hallucinations are more likely to have daytime somnolence, 7 severe sleep fragmentation, 37,38 and vivid dreams. 37,39 Recognition of sleepwake dysregulation in PD with hallucinations led to the hypothesis that hallucinations were caused by intrusion of dream imagery into wakefulness.…”
Section: Sleep Disorders and Autonomic Dysfunctionmentioning
confidence: 99%